The Role of the Glass Ceiling Syndrome in Female Healthcare Workers and Its Association With Telogen Effluvium - Aydin, Delal; Karakoyun, Omer; Ayhan, Erhan (Wiley, 2025)
Background-Objective Telogen effluvium (TE) type hair loss is the most common cause of diffuse and non-scarring alopecia in women and may develop on the basis of many etiological causes. Glass ceiling syndrome, which is a popular research topic especially in recent years, is one of the syndromes that define the invisible barriers that women face in their careers and can cause long-term stress during periods of exposure. Women working in the health sector are frequently exposed to the glass ceiling, and this situation has negative effects on skin health. The aim of the study is to investigate the relationship between glass ceiling syndrome-induced stress and telogen effluvium, which has not been examined before. In addition, another aim of the study is to determine the effect of socio-demographic variables such as age, gender, and education level on stress symptoms telogen effluvium. Materials and Methods This study was conducted on 108 female participants working in University Hospitals. Questionnaires were used to determine how the participants experienced the glass ceiling syndrome, their professional and marital status, and their level of education. In addition, an examination including a pull test and trichoscopy for telogen effluvium disease was performed by specialized doctors. Results 56 (51.85%) of 108 female health workers were diagnosed with telogen effluvium. It was determined that 73 (67.59%) of them had glass ceiling experience. Of the 108 female health workers, 36 were doctors, 44 were nurses, and 28 were other health workers. Regarding their education levels, 36 of them have a master's degree, 18 have a bachelor's degree, 34 have an associate's degree, and 20 have a high school degree. As for marital status, 71 of them were married, 24 of them were single, and 13 of them were divorced. A significant statistical relationship was found between telogen effluvium and glass ceiling syndrome and education and occupational status. At the same time, a significant statistical relationship was found between glass ceiling experience and education and occupational status. Conclusion Glass ceiling syndrome is statistically significantly associated with telogen effluvium in female health workers, and it is emphasized that this situation should not be neglected as a source of intense stress during treatment. In addition, professional and marital status and education levels are also seen to feed this intense stress source.
Keywords: glass ceiling; health worker; stress; telogen effluvium; woman